Karakteristik Persalinan Sectio Caesarea (SC) di RSU Bahagia Makassar - Surmayanti; Fitriana Jufri.P; Sainah (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
Sectio Caesarea (SC) is generally performed when there are certain medical indications, as a termination action with complications. In addition, CS is an alternative to childbirth without medical indications because it is considered easier. As many as 25% of the number of births were carried out to mothers who did not have a high risk for normal delivery or childbirth complications. In 2020, at Happy Makassar Hospital, mothers who gave birth with SC 34.5% were 147 out of 426 deliveries. The purpose of this study was to determine the characteristics of mothers who experienced cesarean delivery at RSU Bahagia Makassar in 2020. This type of research was descriptive analytic with a retrospective approach. The population in this study was data on mothers who experienced cesarean delivery at the Happy Makassar General Hospital in 2020 as many as 147 people. The sample used in as many as 87 respondents with systematic random sampling sampling technique. The instrument used is a checklist. Data analysis consists of univariate analysis. The results showed that the highest number was obtained in the age group of 20-35 years with 56 respondents (64.4%), Bugis ethnicity with a total of 80 respondents (92%), higher education (high school and university) 63 respondents (72.4%). ), working mothers as many as 70 respondents (80.5%), BPJS payment system as many as 63 respondents (72.4%), primipara parity and grandemulti (high risk) with 72 respondents (82.8%), pregnancy intervals more than 2 years as many as 46 respondents (52.9%), good history 56 respondents (64.4%), sc with indications of pre-eclampsia in the mother as many as 28 respondents (32.2%) SC with indications of fetal distress 25 respondents (28.7%). The results of the above study indicate that SC is not always caused by indications but from sociodemographic and medical obstetric factors that must be considered.